Interleukin-22 Influences the Th1/Th17 Axis - Lindahl, Hannes; Olsson, Tomas (Frontiers in Immunology, 2021)
Interleukin-22 (IL-22) is secreted by a wide range of immune cells and its downstream effects are mediated by the IL-22 receptor, which is present on non-immune cells in many organs throughout the body. IL-22 is an inflammatory mediator that conditions the tissue compartment by upregulating innate immune responses and is also a homeostatic factor that promotes tissue integrity and regeneration. Interestingly, the IL-22 system has also been linked to many T cell driven inflammatory diseases. Despite this, the downstream effects of IL-22 on the adaptive immune system has received little attention. We have reviewed the literature for experimental data that suggest IL-22 mediated effects on T cells, either transduced directly or via mediators expressed by innate immune cells or non-immune cells in response to IL-22. Collectively, the reviewed data indicate that IL-22 has a hitherto unappreciated influence on T helper cell polarization, or the secretion of signature cytokines, that is context dependent but in many cases results in a reduction of the Th1 type response and to some extent promotion of regulatory T cells. Further studies are needed that specifically address these aspects of IL-22 signaling, which can benefit the understanding and treatment of a wide range of diseases.